2015
DOI: 10.1111/tbed.12424
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Association of Climate, Weather and Herd Immunity with the Spread of Equine Encephalosis Virus in Horses in Israel

Abstract: It is claimed that the distribution of Culicoides-borne viruses is highly influenced by climate. Equine encephalosis virus (EEV) is a Culicoides-borne orbivirus which affects horses and was recently found to be endemic in Israel. To test whether climate is a crucial factor in the geographical distribution of EEV, we collected blood samples from horses in Israel during the years 2002, 2007 and 2010 and tested them for the abundance of antibodies to EEV. Samples were also collected in 2011 from horses that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 37 publications
1
19
1
Order By: Relevance
“…A recent study of EEV prevalence in Israel found fluctuations in seroprevalence at different time points (65.1% in 2002, 36.5% in 2007, 64.5% in 2010 and 77.2% in 2011) and suggested that certain climatic conditions and herd immunity influenced the risk of exposure (Aharonson‐Raz et al . ). The current seroprevalence in Israel reported here was lower than reported in 2011 ( P < 0.001), and was 58.2%.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…A recent study of EEV prevalence in Israel found fluctuations in seroprevalence at different time points (65.1% in 2002, 36.5% in 2007, 64.5% in 2010 and 77.2% in 2011) and suggested that certain climatic conditions and herd immunity influenced the risk of exposure (Aharonson‐Raz et al . ). The current seroprevalence in Israel reported here was lower than reported in 2011 ( P < 0.001), and was 58.2%.…”
Section: Discussionmentioning
confidence: 97%
“…This correlated with the findings of the previous survey, at all time points (Aharonson‐Raz et al . ), and reflected the fact that the presence of antibodies indicates previous exposure to the virus, and not necessarily a recent one. It is probable that horses older than 7 years of age were exposed to the virus during the 2008 outbreak.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations